Diálogos entre as intervenções assistidas por animais – IAA’S e a psicopatologia fenomenológica: possibilidades clínicas de intervenção em Psicologia - SILVA, Lidiane Verônica Collares da (2019)
The main objective of this dissertation is to present the contributions of Animal-Assisted Interventions for the understanding of psychopathological phenomena. Influenced by the Phenomenology of Edmund Husserl, the German psychiatrist and philosopher Karl Jaspers developed a psychopathology that has as it‘s main characteristic the understanding of the patient's life story and his way of establishing relations with others and with the world, instead of just explaining the objective reality. In the second half of the twentieth century, Brazilian psychiatrist Nise da Silveira and US psychiatrist Boris Levinson consolidated Animal-Assisted Interventions as effective therapy for the follow-up of patients with psychological disorders. In this perspective, this work aims first to describe the history of the man-animal relationship, then to present the possible benefits described in the scientific productions on Animal-Assisted Interventions for existential health and to highlight the contributions of Karl Jaspers‘ Comprehensive Psychopathology and of Edmund Husserl's Phenomenology towards Clinical Psychology. Aiming at the achievement of the established objectives, the present qualitative research adopted the Husserlian phenomenological attitude and method which consisted of searching in electronic databases for scientific research published between the years 2008 and 2018, the original languages being Portuguese or Spanish and having as theme Animal-Assisted Interventions for the promotion of existential health, and in sequence the eidetic and transcendental reductions were done as proposed by Husserl. It was observed that AAI's offer physical, social and psychological benefits to patients with psychological disorders and it was concluded that AAI helps to understand the psychopathological phenomena through the relaxed, affectionate and prejudice-free interaction between the animal and the person, allowing the psychologist to establish better communication with the patient and thus more effectively access their world to understand it. In addition, the animal also exerts the function of catalytic affect being a point of contact of the patient with reality, thus mediating the formation of bonds with other people.